ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING PADA USAHA KECIL DAN MENENGAH UD. DHIPATI JAYA - Fajar Choirul Bahtiar (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2017)
This study aimed to analyze the calculation of the cost of production with the full costing method. This research kind is a quantitative research, which is based on data collected during systematic research of the facts and the properties of the object studied. Data used in this study quantitative data. Sources of data in this research is secondary data. Secondary data in this study is a general overview and financial records from the study. The samples in this study with the technique non probability - purposive sampling.According to analysis carried out can conclude that, the calculation of cost of production conducted business owners with the calculation of cost of production using the full costing method at UD. Dhipati Jaya. There are significant differences in the costs required for production activities for one year.